Formation of special competencies in the process of professional training of future teachers of geography - Borisenko, K. B. (Problems of Engineer-Pedagogical Education, 2018)
This article analyzes the formation problems of professional competence of future teachers of geography, through the educational process organization that ensures the formation and development of special competencies. Technology of specialized competences defined the role of educational and field practice in the process has been disclosed. Workflow based on the competence model of professional. The article provided a detailed analysis of scientific sources on research problems. The work highlighted procedural aspects of special competences formation, the essence of key concepts and their elements. The use of certain forms and methods for achieving the goals of the educational process in the classical university has been justified. It is emphasized that the teacher remains the key figure in the transfer of knowledge and social experience to the younger generation, therefore the quality of education and upbringing depends on the level of his competence as a result. The prospects of the research are the proposal to attribute the development of technology for the formation of certain competences within each academic discipline of the curriculum for the direction of preparation "Geography".